On second Hankel determinant for two new subclasses of analytic functions - T. V. Sudharsan; R. Vijaya (Surveys in Mathematics and its Applications, 2014)
In this paper, we obtain sharp upper bounds for the functional |a2a4 - a32| for functions belonging to S*(α, β) and C(α, β). Our results extend corresponding previously known results.